Technostress among library staff and patrons of the University of the Philippines Diliman libraries - Bachiller, Ross Torrefiel; Dela Torre, Nathalie N. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
Stress is inevitable as libraries and their users deal with the challenges of diminishing human resources, exploding human resources, and accelerating technological change" (LaGuardia, Cheryl). The phenomenon of the computer-related stress or "technostress" has attracted considerable attention among library staff and its users in the library. Technostress is defined as a "modern disease of adaptation caused by the inability to cope with the new computer technologies in a healthy manner" (Brod, 1984). The study focused on the effects of technostress on library staff and patrons of University of the Philippines Diliman Libraries. It was conducted to (1) know if the library staff and patrons suffer the so-called technostress; (2) determine the level of technostress in the four factors namely: physical, emotional, behavioral and psychological factors; (3) determine the causes of technostress; (4) determine the symptoms of technostress; (5) determine if technostress experienced by the library patrons is affected by age, gender, course, year level, frequency of library use, and awareness on information technology in the library; (6) determine if technostress experienced by the library staff is affected by age, gender, civil status, educational background, position in the library, length of service, and awareness on information technology in the library; and (7) know the strategies the library need to have to help library staff and patrons deal with technostress.
Two hundred twenty (220) samples (120 for the library staff and 100 for the library patrons) were chosen as respondents for the two sets of questionnaires. Two hundred eight (208) of which were returned or 95 percent responded. The respondents were classified into two: library staff and library patrons. Out of 120 respondents for the library staff, 108 questionnaires were returned or 90 percent responded while the library patrons have a 100 percent returns. The findings of the study were based on the results of the two sets of questionnaires being answered by the respondents. To test the hypotheses, Analysis of Variance (ANOVA) and regression analysis were used in this study. The level of significance was set at a.05. These statistical techniques became possible with the use of the Statistical Package for Social Sciences (SPSS) software. Descriptive statistics was also used t o present distribution of frequency, mean and standard deviation of the answers according to the independent variables and dependent variables, stressors of tecnostress variables and dependent variables.
Findings of the study reveal that the library staff and patrons suffer the so-called technostress. The library staff have a "low level of technostress" while the library patrons have a "relatively fair amount of technostress." Both the library staff and patrons have a relatively fair amount of tecnostress in terms of the physical factors. In terms of emotional, behavioral and psychological factors, the library staff have "low level of technostress" while library patrons "have a relatively fair level of technostress."
Results of the survey reveal that that causes of technostress in the library according to the library patrons are the following: computer runtime problems and computer information problems which include need to update skills, increased computer use expectations, slow computer speed, slow program speed, and lack of help with a computer problem. On the other hand, library staff cited the following computer hassles : lack of computer expertise, lack of help with a computer problem, slow program speed, slow computer speed, and increased time demands.
Results of the survey indicate that the following are the most cited symptoms of technostress by the library patrons: eyestrain, headaches, muscle tension on shoulders, back pains, overexposure to visual display units, information overload and irritability. On the other hand, common symptoms among library staff are back pains, eyestrain, headaches, increased heart rate, overexposure to visual display units, loss of temper, and unwillingness.
Both ANOVA and regression analysis reveal that library patron's age, gender, course, year level, frequency of library use, and awareness on information technology in the library do not have a significant relationship with physical, emotional, behavioral, and psychological factors of technostress. This is also same with the result yielded by the library staff. The independent variables of the library staff do not have a significant relationship with the physical, emotional, behavioral, and psychological factors of technostress.
Regression analysis reveals that computer runtime problems and computer info. problems do not have a significant relationship with the physical, emotional, behavioral, and psychological factors of technostress for both library staff and library patrons, one-way ANOVA reveal that computer runtime problems do not have a significant relationship with the emotional, and behavioral factors of technostress. "Computer system is down" is the only computer runtime problem that is significantly related to physical factors. In the case of library staff, one-way ANOVA reveals that CRPs do not have significant relationship with the emotional and behavioral factors of technostress. "When the computer is down" is significantly related with physical factors while "slow program speed, computer system is down, lost in the computer, and programming errors" are significantly related with the psychological factors.
In the case of the library patrons, one-way ANOVA reveal that computer info. problems do not have a significant relationship with the physical, emotional and behavioral factors of technostress. Only the statement "increased computer use expectations" is significantly related with the psychological factors. In the case of library staff, ANOVA reveal that computer information problems do not have a significant relationship with the emotional factors of technostresss. Only the statement "increased computer use expectations" among the CIPs show it has significant relationship with the physical factors. "Increased time demands and increased computer use expectations" show significant relationship with the behavioral factors of technostress. The "need to update skills, increased time demands and increased computer use expectations" show significant relationship with the psychological factors of technostress.
Future research can be done to see how technostress affects not only the library staff but also people working/dealing with information technologies in their respective workplace. Using another technique and modern methods in measuring the level of technostress can be a better one in dealing with this particular topic.
To overcome technostress in the library, library staff and patrons recommend the following: (1) education and training about the new information technologies in the library, (2) learning new information technologies one at a time, (3) time management, (4) thinking positively and staying healthy, (5) seeking information about what to do in using the information technologies in the library, (6) setting realistic goals to accomplish, (7) showing an enthusiastic commitment to learning new information technologies in the library, and (8) relaxing through deep breathing. "
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman Libraries; Librarians -- Philippines -- Quezon City; Library employees -- Philippines -- Quezon City; Library users -- Philippines -- Quezon City; Stress (Psychology).